PERAN ORANG TUA BAGI PESERTA DIDIK BERKEBUTUHAN KHUSUS DALAM PENERAPAN PENDIDIKAN INKLUSIF DISEKOLAH DASAR - Resmi Widaningsih; Nenden Ineu Herawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research is motivated by government policy regarding the implementation of Inclusive Education in elementary schools. This research aims to examine more deeply the role of parents in implementing inclusive education. This research was conducted using the literature review method. The results obtained show that the role of parents in implementing inclusive education in schools is very important so that children with special needs can optimize their potential within all the limitations they have. And the role of parents in several previous studies shows that there is a large influence of the role of parents on the achievement of children with special needs.